The PRECISION study protocol: Can cervical stiffness in the second trimester predict preterm birth in high-risk singleton pregnancies? A feasibility, cohort study - Elizabeth Medford; Steven Lane; Andrew Sharp; Angharad Care (PLoS ONE, 2025)
Background Preterm birth (PTB) is a leading cause of neonatal morbidity and mortality. More than 13 million babies are affected globally every year and PTB will contribute to over 900,000 deaths. In the UK, PTB affects 8% of pregnancies and costs more than £260 million annually in neonatal care. Identifying those at risk of this devastating complication of pregnancy and implementing preventative treatment remains a maternal health priority. The mainstay of PTB prevention has been assessment of cervical length (CL) in women at high-risk of PTB. However, CL has limitations, namely it is invasive, user dependent and varies over time through pregnancy. Importantly, not all those who are high-risk with a short CL will subsequently deliver preterm and CL screening doesn’t identify a sub-set of women who have a spontaneous PTB without a short cervix. Therefore, existing care pathways for managing PTB can potentially benefit from additional assessments of risk. Novel ways of assessing cervical structure and function may improve our ability to predict spontaneous PTB and refine preventative intervention. This feasibility study will explore the use of a new antenatal test of cervical stiffness for assessing risk of spontaneous PTB in a high-risk singleton population. Methods PRECISION is a single site prospective, feasibility, cohort study of asymptomatic women with singleton pregnancies at high risk for spontaneous PTB attending an inner-city tertiary maternity hospital in the UK. All study participants will be undergoing routine screening and management of PTB as per local guidance (NICE/Saving Babies Lives guidance) including CL screening with transvaginal ultrasound. Cervical stiffness will be assessed using the Pregnolia System; a novel, licensed, CE-marked, aspiration-based device. A measurement is obtained by applying the device directly to the anterior lip of the cervix, visualised via placement of a speculum, and gives a quantitative assessment of cervical stiffness represented as the Cervical Stiffness Index (CSI, in mbar). Participants will undergo cervical stiffness assessments at up to three timepoints in the second trimester between 14+0 weeks and 25+6 weeks gestation. The cervical stiffness index data will be paired with routine PTB clinic CL measurements taken at the same time points. The primary outcome will focus on the feasibility of using this novel antenatal test in this high-risk population and explore any association between cervical stiffness and PTB. Discussion This is an exploratory study to assess the use of this novel device in clinical practice. Direct comparison between cervical stiffness assessment using the Pregnolia System and CL assessment will determine the acceptability of this new assessment in this population, as well as explore its potential association with PTB. Our findings from this feasibility study will provide data on the potential of this novel device to impact PTB screening and evaluate acceptability of use in a high-risk population. Data on eligibility, recruitment rates and participant feedback will help inform future study design using the device. Trial registration ClinicalTrials.gov NCT05837390